Directional phyllotactic bias in calatheas (Goeppertia, Marantaceae): A citizen science approach. (4th May 2021) - Durrington, Benjamin; Chong, Fiona; Chitwood, Daniel H.; ,
Abstract: Lateral organs arranged in spiral phyllotaxy are separated by the golden angle, ≈137.5°, leading to chirality: either clockwise or counter-clockwise. In some species, leaves are asymmetric such that they are smaller and curved towards the side ascending the phyllotactic spiral. As such, these asymmetries lead to mirroring of leaf shapes in plants of opposite phyllotactic handedness. Previous reports had suggested that the pin-stripe calathea ( Goeppertia ornata ) may be exclusively of one phyllotactic direction, counter-clockwise, but had limited sampling to a single population. Here, we use a citizen science approach leveraging a social media poll, internet image searches, in-person verification at nurseries in four countries and digitally-curated, research-grade observations to demonstrate that calatheas ( Goeppertia spp. ) around the world are biased towards counter-clockwise phyllotaxy. The possibility that this bias is genetic and its implications for models of phyllotaxy that assume handedness is stochastically specified in equal proportions is discussed.